Selection for grain yield and quality in segregating generations of wheat - Andrade,Alessandro Ramos de (2001)
The objective of the work was to combine simultaneous selection for grain yield and technological quality in elite segregating populations of wheat developed by the breeding program of IAPAR. Thirteen populations were chosen according to their potentiality of genetic variability in the F2 generation of the 1997 crop season. One hundred heads were selected from each population and sown as F3 head-rows in the following season. Visual selection of individual head-rows or lines was done for yield potential and maturity. Seeds of the selected lines were evaluated for Sedimentation Values as well as Protein Content. The populations were identified as C1 to C13, representing the different crosses. The number of F2:3 lines selected within populations varied from one to 12. The populations C6, C7, C9, and C13 were classified as early maturity. Two populations (C6 and C9) presented higher potential for grain yield. The populations C12, C3, C8, and C1 were better for mean and variance of sedimentation values. The populations C2, C3 and C11 had a good performance for mean, maximum values and variance of protein content. The data indicates a good potential to obtain advanced lines with higher grain yield associated with a better technological quality.